The efforts of Islamic Education teachers of SMK Dharma Karya in improving the character of students based on the values of the Pancasila student profile - Sarah, Siti; Abdullah Darraz, Muhammad (Lembaga Penelitian dan Pendidikan Mandala, 2024)
This research explores the efforts of Islamic Religious Education teachers, especially teachers of SMK Dharma Karya in trying to improve the character of students based on the values of the Pancasila Student Profile. This study aims to explore the efforts of Islamic Religious Education teachers in shaping the person a lity of students, increasing moral understanding, and strengthening religious identity in accordance with the values of the Pancasila student profile. The subject of Islamic Religious Education has a very significant position in making the personality of students, in line with the values of Pancasila as the ideological foundation of Indonesia. The research method used is qualitative with a case study approach. Obtaining data by means of observation, then direct interviews with Islamic Religious Education teachers, curriculum analysis during daily teaching and learning activities, and documentation of extracurricular activities at SMK. The results of the study are that the Islamic Religious Educati on teacher at SMK Dharma Karya actively practices an approach that is oriented towards the values of Pancasila in improving the character of students. These efforts are related to the use of teaching modules that are relevant to the values of Pancasila, organizing extracur ricular activities, and implementing various interactive education to increase students' understanding of the moral values of Pancasila